A vagyoni értékű jogok apportálhatósága és az egységes szabályozás hiányának problematikája - Lehoczki, Zóra Zsófia (Debreceni Jogi Műhely, 2015)
According to the new Hungarian Civil Code, the funders of the legal entities have to make contributions to the authorised capital and the two forms of these contributions are the contribution is cash and the contribution in kind. The regulation states that proprietary rights can also be transferred to the capital of businness accociations, by those funders, who are entitled to demise them. The judicial practice unanimously defined the rules in those cases, when the object of contribution in kind is a certain proprietary right, especially when the right is connected to the real estate. On the other hand, the Civil Code does not contain a list of those proprietary rights, which can be transferred to the authorised capital and unfortunately, different acts contain different lists of these rights. The three mentioned acts are the following: the personal income tax act, the act about the fees and the accounting act. All of them contain a list of proprietary rights and some of the items are regulated by all the three of them but most of the items are different, which means it is impossible to create an accurate list of these rights. For example, the list in the personal income tax act contains only five items, on the other hand, the accounting act contains two lists and both of them are unfinised. Because of the lack of unified rules, it is impossible to define which proprietary rights can become the objects of contribution in kind and this misfortunate situation causes a lot of unwanted indefinability and states a lot of questions. In my essay I introduce this problem and I use a chart to illustrate the differences between the mentioned lists. In my opinion, this problem could be solved with an unified list, which is normative for every regulation in connection with the proprietary rights or the Civil Code should contain a list of those proprietary rights, which can be the objects of contribution in kind.